2018
DOI: 10.1002/jmv.25081
|View full text |Cite
|
Sign up to set email alerts
|

Sequence analysis‐based characterization and identification of neurovirulence‐associated variants of 36 EV71 strains from China

Abstract: Enterovirus 71 (EV71) is the main pathogen of hand-foot-mouth disease (HFMD) and causes several neurological complications. As new strains of EV71 are constantly discovered, it is important to understand the genomic characteristics of the viruses and the mechanism of virulence. Herein, we isolated five strains of EV71 from HFMD patients with or without neurovirulence and sequenced their whole genomes. We then performed whole genome sequence analysis of totally 36 EV71 strains. The phylogenetic analysis of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…In PJ201984, P2 region had the lowest variation, whereas had the highest different amino acid substitution. The findings revealed that the variations in P2 region might result in changing protein properties, as documented elsewhere [ 33 ]. Similarly, P3 region tended to be unstable because of the highest variation.…”
Section: Discussionsupporting
confidence: 78%
“…In PJ201984, P2 region had the lowest variation, whereas had the highest different amino acid substitution. The findings revealed that the variations in P2 region might result in changing protein properties, as documented elsewhere [ 33 ]. Similarly, P3 region tended to be unstable because of the highest variation.…”
Section: Discussionsupporting
confidence: 78%
“…3D protein, which is an RNA dependent RNA polymerase (RdRp), is responsible for regulating the extension of nucleic acid chains during virus replication. 3D protein crystal is a “right hand” conformation, including “finger”, “palm” and “thumb” domains, that different domains have different functions [ 37 ]. Studies have shown that there was potential interaction between 3D and 5′UTR.…”
Section: Discussionmentioning
confidence: 99%
“…As demonstrated in previous studies in the past few years, certain key amino acid positions on the capsid protein of EV71 determine its replication ability in mice, as well as the susceptibility of mice of different ages to EV71, as well as the virulence of the viruses ( 39 ). As revealed in in-depth studies, certain vital amino acids on the EV71 VP1 protein show a relationship with the mild and severe clinical manifestations of diseases ( 40 ), and the mutations of some amino acid positions on the VP1 may cause neurological symptoms and severe HFMD ( 41 ). The number of cases of severe HFMD attributed to CVA6 have been rising over the past few years ( 42 ), and the mutations of certain amino acid positions on the CVA6 VP1 protein were suggested to correlate with the severity of HFMD ( 43 ).…”
Section: Discussionmentioning
confidence: 99%